A Rare Case Report: Thyrolingual Trunk and The Absence of Facial Artery Determined by 3D-CTA (Annals of Medical Research, 2021)
None
Keywords: Common Carotid Artery; External Carotid Artery; Thyrolingual Trunk; Multidetector Computed Tomography.